1965
DOI: 10.1016/0005-2787(65)90497-1
|View full text |Cite
|
Sign up to set email alerts
|

Some properties of nucleic acids extracted with phenol

Abstract: Preparations of nucleic acids obtained by extraction of mouse liver, HeLa cells and cell fractions with phenol and deoxycholate have been characterized with regard to the differential solubility of ribonucleic acid and deoxyribonucleic acid in ethanol, density-gradient centrifugation and the presence of high-molecular-weight contaminants. Ribonucleic acid obtained by this method is less soluble than deoxyribonucleic acid. It was precipitable with 20 % ethanol, nearly free of deoxyribonucleic acid, but containi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
6
0

Year Published

1967
1967
1977
1977

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 38 publications
(7 citation statements)
references
References 6 publications
1
6
0
Order By: Relevance
“…In experiments in which n-RNA was extracted from the precipitate obtained by treating whole cells with phenol-saturated water (Harris & Watts, 1962) it was found that the rl-RNA was grossly contaminated by polysaccharide. [This finding confirms the observation by Segovia, Sokol, Graves & Ackermann (1965).] When the labelled n-RNA prepared in this way was subjected to sucrose-density-gradient centrifugation, a pellet of material containing a high proportion of the radioactivity was deposited at the bottom of the tube.…”
supporting
confidence: 91%
“…In experiments in which n-RNA was extracted from the precipitate obtained by treating whole cells with phenol-saturated water (Harris & Watts, 1962) it was found that the rl-RNA was grossly contaminated by polysaccharide. [This finding confirms the observation by Segovia, Sokol, Graves & Ackermann (1965).] When the labelled n-RNA prepared in this way was subjected to sucrose-density-gradient centrifugation, a pellet of material containing a high proportion of the radioactivity was deposited at the bottom of the tube.…”
supporting
confidence: 91%
“…The presence of certain polysaccharides which can appear as satellite bands in CsCI density gradients has been observed in DNA preparations of E. coli (36), photosynthetic bacteria (42), blue-green algae (15), Drosophila (34), and HeLa cells (37). Another possible source of error in the interpretation of these results would derive from the presence of an uncommon base in a portion of the DNA molecule, thus leading to a difference in buoyant density (35).…”
Section: Discussionmentioning
confidence: 99%
“…This fundamental difference in the behavior of dextrans that differed in molecular weight was used in the CsCl density gradient experiments that follow. Band formation by glycogen in CsCl density gradients has also been reported (1,28) and is included in Fig. 11 for reference.…”
Section: Resultsmentioning
confidence: 79%